1D Cu@Ni nanorods anchored on 2D reduced graphene oxide with interfacial engineering to enhance microwave absorption properties. Issue 44 (3rd November 2017) - Zhao, Biao; Liang, Luyang; Deng, Jiushuai; Bai, Zhongyi; Liu, Junwei; Guo, Xiaoqin; Gao, Ka; Guo, Wenhui; Zhang, Rui
Abstract : In this work, one-dimensional core–shell Cu@Ni nanorods which were anchored on two dimensional reduced graphene oxide (rGO) heterostructures were successfully prepared by a simple co-reduction method. Abstract : In this work, one-dimensional core–shell Cu@Ni nanorods which were anchored on two dimensional reduced graphene oxide (rGO) heterostructures were successfully prepared by a simple co-reduction method. The characteristics of Cu@Ni/rGO composites were measured and collected by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy and Raman spectroscopy. The formation mechanisms of these unique Cu@Ni nanorods–rGO heterostructures were discussed in detail. Compared with pure Cu@Ni and rGO, the Cu@Ni/rGO composite showed strong microwave absorption performance with a minimal reflection loss value of −41.2 dB at 8.8 GHz. The excellent microwave absorption properties could be attributed to the suitable impedance match, eddy current loss, multiple reflection and intense interfacial polarization of multiple interfaces existing in Ni/Cu, Cu@Ni/rGO, Ni/rGO, and Cu/rGO systems. The effective bandwidth with a reflection loss lower than −10 dB can be tuned in a frequency range of 3.8–18 GHz with an absorber thickness of 1.0–4.0 mm. This proves that the Cu@Ni/rGO heterostructure is a promising candidate as a highly efficient and lightweight absorber in C (4–8 GHz), X (8–12 GHz) and Ku (12–18 GHz) bands.